Amazigh spell checker using Damerau-Levenshtein algorithm and N-gram - Youness Chaabi; Fadoua Ataa Allah (Journal of King Saud University: Computer and Information Sciences)
Natural language processing (NLP) is a rapidly growing research field in computer science and cognitive science. Automatic correction of lexical errors is one of the applications of NLP, which aims to detect errors in the text and suggest possible corrections based on computer and linguistic models. After a state of the art and a comparison of spelling correction approaches, we developed a spelling error correction system for the Amazigh language combining the Damerau-Levenshtein algorithm and N-gram. This tool will propose possible corrections for each misspelled word in the text. Successful tests have been carried out using an Amazigh corpus.